GAP BOARD AS AN ALTERNATIVE MEDIA TO MOTIVATE TEACHING STUDENTS (PRE-SERVICE TEACHER PERCEPTION IN TEACHING MEDIA) - Hariyani, Yunita; Athena, Tera; Kusuma, Rendra (Universitas Madura, 2026)
This research employed a qualitative descriptive approach aimed at providing a comprehensive and detailed description of learning phenomena using everyday language. The study examined students’ perceptions of the use of Gap Board media in the learning process. The findings indicate that the Gap Board is perceived as interesting, challenging, and effective in enhancing student motivation, learning activities, and overall learning experience. The dominance of agree and strongly agree responses across all indicators suggests a positive student response to learning that integrates visual elements, challenges, and active engagement. Furthermore, the challenging elements embedded in the Gap Board contribute to increased learning motivation, supporting intrinsic motivation theory, which posits that enjoyable yet challenging activities foster sustained interest and engagement.